1998
DOI: 10.1068/p271087
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Depth and Slant from Texture in Three-Dimensional Scenes

Abstract: The perception of depth and slant in three-dimensional scenes specified by texture was investigated in five experiments. Subjects were presented with computer-generated scenes of a ground and ceiling plane receding in depth. Compression, convergence, and grid textures were examined. The effect of the presence or absence of a gap in the center of the display was also assessed. Under some conditions perceived slant and depth from compression were greater than those found with convergence. The relative effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
5
28
1
Order By: Relevance
“…The observers' judgments of slant in Experiment 1 (see Figure 3) were generally accurate: Our observers did not exhibit the underestimation that has been obtained in many previous studies (see, e.g., Andersen et al, 1998;Rosas et al, 2004;Saunders, 2003;Todd et al, 2005). Given that our surfaces were physically slanted in depth (instead of being simulated computationally and then displayed on a frontoparallel monitor or projection screen), it is possible that other monocular factors, such as accommodative blur (Ciuffreda, Wang, & Vasudevan, 2007;Frisby, Buckley, & Horsman, 1995;Watt, Akeley, Ernst, & Banks, 2005), contributed to the accurate performance of our observers in Experiment 1.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…The observers' judgments of slant in Experiment 1 (see Figure 3) were generally accurate: Our observers did not exhibit the underestimation that has been obtained in many previous studies (see, e.g., Andersen et al, 1998;Rosas et al, 2004;Saunders, 2003;Todd et al, 2005). Given that our surfaces were physically slanted in depth (instead of being simulated computationally and then displayed on a frontoparallel monitor or projection screen), it is possible that other monocular factors, such as accommodative blur (Ciuffreda, Wang, & Vasudevan, 2007;Frisby, Buckley, & Horsman, 1995;Watt, Akeley, Ernst, & Banks, 2005), contributed to the accurate performance of our observers in Experiment 1.…”
Section: Methodssupporting
confidence: 77%
“…Past research on the perception of slant, conducted mostly with computer-generated texture patterns, has typically shown underestimation (e.g., Andersen et al, 1998;Gibson, 1950b;Newman et al, 1973;Rosas et al, 2004;Saunders, 2003;Todd et al, 2005). The observers in our Experiment 2 also exhibited underestimation when they judged the surface slants by using magnitude estimation (see Figure 8).…”
Section: Discussionmentioning
confidence: 46%
“…Nevertheless, a number of studies in the past have shown that the visual system is more effective at deriving the orientation and depth of a surface from linear perspective than from compression gradient information (Andersen, Braunstein, & Saidpour, 1998;Blessing et al, 1967;Braunstein & Payne, 1969;Gillam, 1970). To verify whether this conclusion holds for the process of representing the ground surface in distance perception within a natural 3-D environment, the present experiment measured judged distances in two different texture background conditions (a compressing vs. an equal-spacing condition).…”
Section: Experiments 7 Linear Perspective Versus Compression Gradientmentioning
confidence: 74%
“…The perception of 3-D scenes usually involves an integration of information about overall scene depth, the layout or relative position of objects in the scene, and the properties of the objects within the scene (Andersen, Braunstein, & Saidpour, 1998). The information may be either viewer centered, providing absolute or relative distances from the observer to the locations in the scene, or object centered, providing distances among locations in the scene.…”
mentioning
confidence: 99%
“…The information may be either viewer centered, providing absolute or relative distances from the observer to the locations in the scene, or object centered, providing distances among locations in the scene. There is a considerable body of research focusing on the effectiveness of different sources of information used in the perception of individual objects and surfaces in 3-D scenes, such as texture (e.g., Andersen et al, 1998;Stevens, 1981;Todd & Akerstrom, 1987), motion parallax (e.g., Braunstein & Andersen, 1981;Rogers & Graham, 1979), and binocular disparity (e.g., Gillam, Flagg, & Finlay, 1984;Norman & Todd, 1998). Another stream of research has studied the integration of different cues in indicating depth, such as motion and disparity (e.g., Turner, Braunstein, & Andersen, 1997), motion and texture (e.g., Braunstein, 1968), and disparity and shading (Tittle, Norman, Perotti, & Phillips, 1998).…”
mentioning
confidence: 99%